Phytoextraction of Lead and Zinc in Garages in Southern Benin using Lantana camara - IDOHOU1, Jeanne A.; ADOUNKPE, GNONLONFOUN JULIEN (My University, 2020)
The ability of Lantana camara to accumulate lead (Pb) and zinc (Zn) was studied in a continuous phytoremediation experiment in the soils of four garages in southern Benin. The soil collected in each garage using a manual auger at a depth of 30cm by the diagonal method was characterized. The cultivation of about twenty L. camara seedlings from nursery was conducted for each garage on a 2m x 1.5m spacing. The experiment was carried out over 12 weeks from April to June 2018. Sampling was collected from each garage every week during the first month, then every two weeks during the second month and then a last sampling was done during the third month. The levels of lead and zinc in soils and dry biomasses of plants were measured using the dithizone and Zincon methods, respectively. The results of these analyses showed an increase in the content of lead and zinc in dry biomasses with the wastes. The concentrations of lead and zinc in the soil range from 10.31 mg/kg to 11.45 mg/kg and from 40.72mg/Kg to 193.03mg/Kg. The high accumulation capacity of L. camara was recorded in the first eight weeks for lead and varied and increased over the twelve weeks for Zinc. In this continuous phytoremediation experiment, Lantana camara absorbed up to 68.32 mg/Kg of lead and 7662.67 mg/Kg of zinc.
Keywords: Lantana camara; car garage; concentration; heavy metals; phytoremediation